Daughter of the house - Thomas, Rosie (The Overlook Press, 2015)
"Nancy Wix, daughter of stage impresarios Eliza and Devil, is a born performer. But she is set apart, even from her unusual family, by the visions she has seen since she was a child. When a gifted medium reveals a way for Nancy to harness her troubling powers to keep the Wix's struggling theatre afloat, she grasps the opportunity with a desperate intensity. This is the age of spiritualism, and Nancy will see her star rise in a time when families decimated by World War I are anxious to believe their dead loves ones are not out of reach"--Dust jacket.